2023
DOI: 10.3390/pharmaceutics15092310
|View full text |Cite
|
Sign up to set email alerts
|

Pyrenebutyrate Pt(IV) Complexes with Nanomolar Anticancer Activity

Anife Ahmedova,
Rositsa Mihaylova,
Silviya Stoykova
et al.

Abstract: Research on platinum-based anticancer drugs continuously strives to develop new non-classical platinum complexes. Pt(IV) prodrugs are the most promising, and their activation-by-reduction mechanism of action is being explored as a prospect for higher selectivity and efficiency. Herein, we present the anticancer potency and chemical reactivity of Pt(IV) complexes formed by linking pyrene butyric acid with cisplatin. The results from cytotoxicity screening on 10 types of cancer cell lines and non-malignant cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…These studies exemplify the promising anticancer potential of Ru­(II)-arene complexes of TSCs. Furthermore, researchers have also evaluated the bioactivity of substituted naphthenyl, and anthracenyl groups incorporated ligands in transition metal-arene complexes. , Thus, higher analogues of pyrenyl residue incorporated into TSCs can be explored for anticancer applications in future. The molecular structures of some of the Ru­(II)-chemotherapeutic drug candidates under clinical/preclinical trials are shown in Figure . …”
Section: Introductionmentioning
confidence: 99%
“…These studies exemplify the promising anticancer potential of Ru­(II)-arene complexes of TSCs. Furthermore, researchers have also evaluated the bioactivity of substituted naphthenyl, and anthracenyl groups incorporated ligands in transition metal-arene complexes. , Thus, higher analogues of pyrenyl residue incorporated into TSCs can be explored for anticancer applications in future. The molecular structures of some of the Ru­(II)-chemotherapeutic drug candidates under clinical/preclinical trials are shown in Figure . …”
Section: Introductionmentioning
confidence: 99%